X‐linked Charcot‐Marie‐Tooth disease type 6 (CMTX6) patients with a p.R158H mutation in the pyruvate dehydrogenase kinase isoenzyme 3 gene. Issue 1 (March 2016) - Kennerson, Marina L.; Kim, Eun J.; Siddell, Anna; Kidambi, Aditi; Kim, Sung M.; Hong, Young B.; Hwang, Sun H.; Chung, Ki W.; Choi, Byung‐Ok
Abstract: Charcot‐Marie‐Tooth disease (CMT) is the most common inherited peripheral neuropathy. Mutations in the pyruvate dehydrogenase kinase isoenzyme 3 ( PDK3 ) gene have been found to cause X‐linked dominant CMT type 6 (CMTX6). This study identified the p.R158H PDK3 mutation after screening 67 probable X‐linked CMT families. The mutation fully segregated with the phenotype, and genotyping the family indicated the mutation arose on a different haplotype compared with the original Australian CMTX6 family. Results of bisulphite sequencing suggest that methylated deamination of a CpG dinucleotide may cause the recurrent p.R158H mutation. The frequency of the p.R158H PDK3 mutation in Koreans is very rare. Magnetic resonance imaging revealed fatty infiltration involving distal muscles in the lower extremities. In addition, fatty infiltrations were predominantly observed in the soleus muscles, with a lesser extent in tibialis anterior muscles. This differs from demyelinating CMT1A patients and is similar to axonal CMT2A patients. The clinical, neuroimaging, and electrophysiological findings from a second CMTX6 family with the p.R158H PDK3 mutation were similar to the axonal neuropathy reported in the Australian family.